Friendship in politics, community, populism and liberalism: a response to Nordin and Smith. Issue 4 (2nd October 2018) - Roberts,
Abstract : ABSTRACT This response looks first at the authors' suggestion that friendship is a useful concept for understanding and shaping politics and agrees that it is commonly used, though its meaning is commonly understood as different from the one proposed by the authors. Secondly, it focuses on their argument that friendship could serve as 'a politics beyond community', asking if friendship is not more easily understood as a sub-set of community or the means to building a community of the like-minded. Thirdly, it comments on the links of community and populism, noting that the populism is a recurring phenomenon and not exclusively rooted in European thought. Lastly, while agreeing that the proposed ethos is welcome, it asks how much it differs from other ideas, notably liberal, universal values that are built on the idea of individual rights, including a belief in tolerance, moderation and respect for political views that differ from one's own. This is a reply to:Nordin, A. H. M. and Smith, G. M. 2018. "Friendship and the new politics: beyond community". Global Discourse . doi: 10.1080/23269995.2018.1505348